PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP KEMAMPUAN MENULIS SURAT RESMI SISWA KELAS VII SMP NEGERI 7 PEMATANGSIANTAR - Sihombing, Rohmayani Gusti; Sirait, Jumaria; Doclas Belmondo Silitonga, Immanuel; Riahni Saragih, Vita; Agkris Tambunan, Marlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACTThis study aimed to determine the effect of the Project Based Learning (PjBL) model on the official-letter writing ability of seventh-grade students at SMP Negeri 7 Pematangsiantar. This study employed a quantitative approach with a quasi-experimental design using a Two-Group Pretest-Posttest Design. The population of this study consisted of all seventh-grade students at SMP Negeri 7 Pematangsiantar. The sample consisted of 60 students, comprising 30 students from class VII-6 as the experimental class and 30 students from class VII-9 as the control class. Data were collected through an official-letter writing test in the form of a pretest and posttest. The data were analyzed using descriptive statistics, a normality test, a homogeneity test, and hypothesis testing using the Independent Samples t-Test.The results showed that the mean score of the official-letter writing ability of the experimental class increased from 61.00 on the pretest to 85.00 on the posttest, while the mean score of the control class increased from 60.50 to 73.83. The results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05. Therefore, Ha was accepted and Ho was rejected. It can be concluded that the use of the Project Based Learning (PjBL) model had a significant effect on the official-letter writing ability of seventh-grade students at SMP Negeri 7 Pematangsiantar.